Helleborus purpurascens Waldst. et Kit. (Ranunculaceae) – рідкісний вид флори Європи на східній межі ареалу - Melnyk, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
Geographical distribution, habitats and modern state of populations of Helleborus purpurascens Waldst. et Kit. (Ra nunculaceae) in Ukraine (in the eastern limit of area) are described. H. purpurascens is rare species of European flora, included to Red Data Books of Poland, Czech and Slovakia Republics, Red List of plants of Hungary and regional red lists of Khmelnytsky and Chernivtsi regions of Ukraine. This species is endemic of Europe. The area of H. purpurascens occupied Balkan and Carpathian Mountains and Podolsk Upland. Main natural habitats of H. purpurascens in Ukraine are deciduous beech and oak forests. Modern state of populations on this species are depended of state of habitate disturbance. Homeostatic populations with complete ontogenetic state are prevail in antrogeneticly not disturbed habitats. The felling of the forests are caused disruption of age structure and entire degradation of populations. Recommendations for improvement in situ protection of H. purpurascens in Ukraine are proposed.